Solar Wind Turbulence Outlined Through Magnetic Islands and Nonlinear Waves - Sharma, R. P.; Gaur, Nidhi; Sharma, Swati; Mishra, M. K. (Frontiers in Astronomy and Space Sciences, 2022)
Various space missions and observations over past many decades have provided unexampled details about the nature of solar wind, the acceleration mechanism and different nonlinear phenomena responsible for energy transfer and turbulence in the interplanetary space. This review focuses on the role of Alfvénic fluctuations- both Kinetic Alfvén wave (KAW) and dispersive Alfvén wave (DAW) in driving solar wind turbulence and magnetic reconnection at 1 A.U. The process of filamentation has been studied through a nonlinear coupling system of KAW/IAW (Ion Acoustic Wave) and relatively high frequency pump KAW (HKAW i.e. frequency less then ion cyclotron frequency) in the presence of LKAW (Low frequency KAW i.e. frequency very much less then ion cyclotron frequency) perturbation by formulating their dynamical equations in the presence of ponderomotive force and using the numerical results for the same. A simplified model is presented to have a deeper insight of the evolution pattern using the results of simulation. The formation of coherent structures and current sheets using numerical and semi analytical approach is elaborated near the magnetic reconnection sites. In addition to this, the relevance of the generated turbulence is also depicted through the energy spectrum by examining the spectral index which is noticeable in determining the energy cascade down to smaller scales.